Fungsi dan Kewenangan Dinas Energi dan Sumber Daya Mineral Provinsi Banten dalam Pemberian Rekomendasi Perizinan Pertambangan di Kota Cilegon Berdasarkan Undang-Undang Nomor 3 Tahun 2020 tentang Pertambangan,Mineral dan Batubara - Sinta Dewi Murni; Ikomatussuniah; Ahmad Rayhan (SM Institute, 2026)
This study examines the functions and authority of the Banten Provincial Energy and Mineral Resources Agency in issuing mining licensing recommendations in Cilegon City and identifies the obstacles affecting their implementation. It applies an empirical juridical method with a descriptive-analytical approach. Primary data were obtained through interviews with officials of the Banten Provincial Energy and Mineral Resources Agency, the Legal Division of the Cilegon City Regional Secretariat, and a mining business representative. Secondary data were collected from legislation, licensing documents, books, and scholarly articles. The data were qualitatively analysed using authority and supervision theories. The findings show that the agency conducts administrative verification, technical evaluation, spatial conformity assessment, environmental document review, and field inspection when required. These activities are carried out through the sectoral ESDM service integrated with the Online Single Submission Risk-Based Approach as part of the authority delegated by the central government. Technical recommendations function as a preventive control instrument before the licensing process is continued by the competent authority. Three principal obstacles were identified: incomplete or inconsistent documents, suboptimal inter-agency coordination, and limited direct supervision of mining activities. Stronger verification standards, data interoperability, cross-sectoral coordination, and field supervision are required to improve legal certainty, administrative order, and sustainable mining governance.